Treatment and associated outcomes of type 2 diabetes mellitus patients with a cardiovascular comorbidity and comparison with guideline recommendations: a German claims data analysis - Aberle, Jens; Dürschmied, Daniel; Grond, Martin; Lehrke, Michael; Martin, Stephan; Tröbs, Sven-Oliver; Schultze, Michael; Kossack, Nils; Richter, Lena Margareta; Gabler, Maximilian (Cardiovascular diabetology, 2025)
Type 2 diabetes mellitus (T2DM) patients are at high risk for micro- and macrovascular complications, and cardiovascular (CV) events are a major cause of their increased risk of early death. Despite well-established treatment guidelines for the management of CV disease in T2DM, little is known about the real-world implementation of these guidelines.
Gesehen am 23.10.2025